CLIL : the added value to english language teacher education for young learners - Ellison, Maria (2015)
As teaching English to young learners (TEYL) of primary school age becomes engendered in more national curricula across Europe, deep reflection is required of those involved in teacher education as to how language teachers should be prepared for the reality of the primary educational context when it is they that are entrusted with this responsibility. In order to avoid the potential pitfalls often brought about when a new ‘subject’ enters a curriculum, such as isolation and disjuncture, teacher education for primary English language teachers needs to consider educational approaches that embrace the ethos of holistic, interdisciplinary learning which is at the heart of primary education. One such approach is Content and Language Integrated Learning (CLIL), in which school subjects are taught through a foreign language. This paper examines the potential contribution of CLIL to English language teacher education programmes given that its underlying principles and methodology focus on the combined development of Content, Communication, Cognition and Culture, all vital elements in the primary curriculum. CLIL obliges language teachers to look beyond language and address other essential learner needs. It improves teachers’ knowledge of the primary curriculum, makes them aware of the responsibility to educate the ‘whole’ child, develops their understanding of the cognitive and linguistic demands of this level of education, and the important role of language across the curriculum. CLIL also unites language and generalist (primary) teachers in partnerships where they work together to achieve broad educational goals. A consideration of CLIL in foreign language teacher education is necessary if primary English language teachers are to make a meaningful contribution to the education of young learners in primary school contexts.